Characterization of Binding Sequences for Butyrolactone Autoregulator Receptors in Streptomycetes - Kinoshita, Hiroshi (American Society for Microbiology, 1999)
BarA of Streptomyces virginiae is a specific receptor protein for a member of butyrolactone autoregulators which binds to an upstream region of target genes to control transcription, leading to the production of the antibiotic virginiamycin M(1) and S. BarA-binding DNA sequences (BarA-responsive elements [BAREs]), to which BarA binds for transcriptional control, were restricted to 26 to 29-nucleotide (nt) sequences on barA and barB upstream regions by the surface plasmon resonance technique, gel shift assay, and DNase I footprint analysis. Two BAREs (BARE-1 and BARE-2) on the barB upstream region were located 57 to 29 bp (BARE-1) and 268 to 241 bp (BARE-2) upstream from the barB translational start codon. The BARE located on the barA upstream region (BARE-3) was found 101 to 76 bp upstream of the barA start codon. High-resolution S1 nuclease mapping analysis revealed that BARE-1 covered the barB transcription start site and BARE-3 covered an autoregulator-dependent transcription start site of the barA gene. Deletion and mutation analysis of BARE-2 demonstrated that at least a 19-nt sequence was required for sufficient BarA binding, and A or T residues at the edge as well as internal conserved nucleotides were indispensable. The identified binding sequences for autoregulator receptor proteins were found to be highly conserved among Streptomyces species.